Efektifitas Waktu Pelaksanaan Pekerjaan Rekonstruksi Jalan Wolo –Batas Kota Kolaka – Rate Rate - Ahmad, Ahmad; Lakawa, Irwan; Rachmat, La Ode Musa (Sultra Civil Engineering Journal (SCiEJ), 2020)
By analyzing the implementation of this project work is expected to know the comparison between the plan and the realization, the effectiveness of the time executor and factors affecting the effectiveness of implementation on road reconstruction work. The medhod used in this research is to take data in the form of curve S, RAB, back up data, weekly report, montly report and questonnaire data for factors that influence the implementation of extreme weather factors, coordination factor between agencies, factors of delay in material testing, experience of executor and tool availability factor with analysis using SPSS mean rank application. Based on the result of reviewing and data analyzing, the time that occurs in the implementation of the road reconstruction work has been delayed due to get minus deviation value, than is in February – 0,225 %, March – 4,855 %, April -10,118 %, May – 20,606 %, June – 37,379 %, July – 57,111 %, August – 55,379 %. Data for the value of the effectiveness of work on aggregate class B in April 0,4 months Mei 0,87, June 0,90, July 0,87, August 0,87. Aggregate of class A in May 0,13, June 0,17, month of July 0,35, month of August 0,90 and work of asphalting AC-BC its effectiveness value is 0,4. The data for factor affecting effectveness of implementation based on mean rank analysis ie extreme weather 3,0, coordination between intances 3,30, material testing delay 2,90, execution experience 2,90, availability of tools 2,90s